A unified approach toward the rational design of selective low nanomolar human neutrophil elastase inhibitors1. Issue 64 (12th July 2015) - Areias, L. R. P.; Ruivo, E. F. P.; Gonçalves, L. M.; Duarte, M. T.; André, V.; Moreira, R.; Lucas, S. D.; Guedes, R. C.
<x xml:space="preserve">Abstract</x> A computer-aided campaign boosted the discovery of potent human neutrophil elastase (HNE) inhibitors.